Reliability of variable speed pumped-storage plant - Joseph, Anto; Chelliah, Thanga Raj; Lee, Sze Sing; Lee, Kyo Beum (Electronics (Switzerland), 2018)
The multi-channel (MC) back-to-back voltage source inverter (VSI)-fed doubly fed induction machine (DFIM) is emerging as a highly interesting topic in large-rated variable speed pumped-storage power plants (PSPP) in view of cost, optimal efficiency, and space requirements. Although the VSI is the fundamental part of the drive controlling the active/reactive power of the plant, redundancy is presently not adopted in practice causing the unit as a whole to shut down upon a failure in the converter and control circuit. This paper evaluates a large-rated (250 MW) DFIM-fed variable-speed unit of a PSPP in terms of its reliability and availability. A Markov model is developed to assess the reliability of the drive based on a number of factors including survivability and annual failure rate (FIT). Further, the Markov model is applied to different PSPPs for comparison of reliability among them.
Keywords: Doubly fed induction machine; Markov model; Pumped-storage power plant; Reliability